Frontier of Self and Impact Prediction - Cléry, Justine; Hamed, Suliann Ben (Frontiers in Psychology, 2018)
The construction of a coherent representation of our body and the mapping of the space immediately surrounding it are of the highest ecological importance. This space has at least three specificities: it is a space where actions are planned in order to interact with our environment; it is a space that contributes to the experience of self and self-boundaries, through tactile processing and multisensory interactions; last, it is a space that contributes to the experience of body integrity against external events. In the last decades, numerous studies have been interested in peripersonal space (PPS), defined as the space directly surrounding us and which we can interact with (for reviews, see Cléry et al., 2015b; de Vignemont and Iannetti, 2015; di Pellegrino and Làdavas, 2015). These studies have contributed to the understanding of how this space is constructed, encoded and modulated. The majority of these studies focused on subparts of PPS (the hand, the face or the trunk) and very few of them investigated the interaction between PPS subparts. In the present review, we summarize the latest advances in this research and we discuss the new perspectives that are set forth for futures investigations on this topic. We describe the most recent methods used to estimate PPS boundaries by the means of dynamic stimuli. We then highlight how impact prediction and approaching stimuli modulate this space by social, emotional and action-related components involving principally a parieto-frontal network. In a next step, we review evidence that there is not a unique representation of PPS but at least three sub-sections (hand, face and trunk PPS). Last, we discuss how these subspaces interact, and we question whether and how bodily self-consciousness (BSC) is functionally and behaviorally linked to PPS.